Effects of temperature and water availability on the productivity, physiology and isotopic (δ¹³c) discrimination of two Myrtacae species: Eucalyptus grandis and Syzygium guineense - Mbuyisa, Yenziwe Ngenzeni (Stellenbosch : Stellenbosch University, 2025)
Thesis (MSc)--Stellenbosch University, 2025.